Exploring the girl-child’s body-mind crisis in Mahachi-Harper’s Echoes in the shadows (Journal for Studies in Humanities and Social Sciences, 2015)
In its exploration of childhood, this article navigates the contours of the notion “girl-child” as the “sulbatern” or the “other” in Mahachi-Har per’s narrative, Echoes in the shadows. Also, in its articulation of the complexities of “childhood” in African Literature, the article endeavours to address broader issues such as the use and abuse of cultural practices in “knowledge legitimation” (Nnaemeka, 1997, p. 1) in Mahachi-Har per’s narrative. Premised on the feminist theory, the article shows how issues in feminism such as visibility, marginality, victimhood, silence, agency and subjectivity are problematised in the narrative. More importantly, the article argues that the “experience of childhood as a time of innocence, security, self-worth, and contribution to family and community” (Kurth-Schai, 1997, p. 193) is a distant fantasy for most children as shown by Vaida in Mahachi-Harper’s Echoes in the shadows. Even so, the writer is aware of the dangers of universalising the child’s experiences as monolithic and thus will contextualise the child’s experiences, specifically, the girl-child, within the Shona culture in Echoes in the shadows. The mental and physical plight of the girl-child is explored within the context in which the book is set and reveals how she is trapped in a familial institution that is supposed to protect and nurture her. Through the young girl Vaida, Mahachi-Harper shows how deeply violence is embedded in the domestic domain (Bal, 1988, p. 231). The paper concludes that it is difficult to attain social justice in a culture or society that pits male against female and adult against child; hence the paper advances for a child-centred social ethic which provides a more appropriate premise for addressing the needs and interests of the girl-child than the feminist approach.